Does captivity affect the aerobic culturable gastrointestinal and respiratory microflora of the Indian Gyps vultures? - Shringarpure, Rohan Narendra; Kulkarni, Mandar Dilip; Sawant, Chhaya; Bhagwat, Ashok; Prakash, Vibhu (Journal of the Bombay Natural History Society (JBNHS), 2015)
Long-term captivity is known to alter the microflora of animals. This alteration in microflora could be because of diet or the environment, and might affect the normal physiological functions of the animal. This study was conducted to assess whether captivity had altered the microflora of the critically endangered Gyps vultures of three species - Longbilled Vulture, White-rumped Vulture, and Slender-billed Vulture - at the BNHS-Vulture Conservation Breeding Centre, Pinjore, Haryana. Cloacal and choanal swabs from 17 captive vultures, hatched at the Centre, were collected and analyzed for aerobic culturable bacteria. The birds were hatched in captivity and were in captivity from hatching till the time of sampling. Results from these samples were compared with the patterns obtained from 32 wild hatched vultures held in captivity at the centre, with patterns from four free ranging Red-headed Vultures used as control. No significant differences were found between the microflora of the captive and wild hatched vultures held in captivity, thus indicating that captivity did not affect the microflora of the captive hatched vultures. This study is the first of a series of planned studies, to ensure that the captive hatched vultures remain healthy and fit to be released in the wild.